Unscripted Emotions: Analyzing Expressive Speech Acts in the Korean Talk Show Titled No Prepare - Cassandra Putri Vincka Azzahra; Putu Pramania Adnyana (Universitas Negeri Medan, 2025)
Most studies on expressive speech acts in Korean have primarily focused on theoretical frameworks, with limited attention to their use in informal and spontaneous contexts. Addressing this gap, the present study investigates expressive speech acts in the YouTube reality show No Prepare Season 2. Using a qualitative descriptive method, the research centers on the host’s utterances to examine the forms and functions of expressive speech acts. The findings indicate that most expressive acts are delivered indirectly, reflecting the host’s preference for implicit emotional expression. Emotions such as happiness and surprise were the most frequently observed, reinforcing the show’s lighthearted and positive tone. In contrast, expressions of anger and dislike were strategically employed as humor to highlight the guests' appeal. This demonstrated that expressive speech in this context serves both emotional and entertainment purposes. Emotional openness was greater in close or equal relationships, while social distance led to more restrained expression. Nevertheless, the host’s communicative style which marked by humor, politeness, and spontaneity enabled smooth and engaging interactions across different social dynamics.